Analysis of lnterdependence Between Air Transfer of LC-ltems and Geographical Distances - Kovač-Striko, Elizabeta; Andabaka, Goranka; Rakić, Estera (Promet - Traffic&Transportation, 2012)
Using the data collected by the Universal Postal Union, thepaper studies the con·elation between the delive1y time of ordinarymail items by air and the geographical distance. lt is foundthat there is poor linear co’elation. The reasons for the obtainedresults are discussed and a suggestion for improvementis offered, which would mean improvement in the quality of theconsidered postal service.